Lowering interleukin-1 activity with anakinra improves myocardial deformation in rheumatoid arthritis. Issue 18 (28th May 2009) - Ikonomidis, I; Tzortzis, S; Lekakis, J; Paraskevaidis, I; Andreadou, I; Nikolaou, M; Kaplanoglou, T; Katsimbri, P; Skarantavos, G; Soucacos, P; Kremastinos, D Th
Abstract : Objective: Inhibition of interleukin-1 activity improves nitro-oxidative stress, endothelial and coronary function. The authors investigated (a) the association of nitro-oxidative stress and endothelial function with myocardial deformation, (b) the effects of anakinra, an interleukin-1a receptor antagonist on myocardial deformation in patients with rheumatoid arthritis (RA). Methods: The authors compared 46 RA patients to 23 normal controls. 23 patients received anakinra (150 mg subcutaneously once daily) and 23 patients a 5-mg increase of prednisolone dose for 30 days. At baseline and post-treatment this study assessed (a) the left ventricular (LV) longitudinal, circumferential and radial strain and strain rate, using speckle tracking echocardiography, (b) the coronary flow reserve (CFR), (c) the flow-mediated endothelial-dependent dilation of the brachial artery (FMD) and (d) nitrotyrosine (NT) and malondialdehyde blood levels. Results: Patients had impaired baseline myocardial deformation indices compared to controls (p<0.05). CFR and NT levels were related to longitudinal strain, systolic and diastolic strain rate, circumferential strain and systolic strain rate (p<0.05). FMD was related to longitudinal and circumferential diastolic strain rate (p<0.01). Compared to baseline, anakinra-treated patients increased the longitudinal strain (−17.8% (3.7%) vs −22.1% (3.5%)), systolic (−1.02 (0.23) l/s vs −1.25 (0.23) l/s) and diastolic (0.96 (0.37) l/s vs 1.20 (0.39) l/s) longitudinal strain rate, circumferential strain and strain rate (p<0.05 for all comparisons). No significant changes were observed among prednisolone-treated patients Conclusions: Myocardial deformation is impaired in RA patients and is related to nitro-oxidative stress and endothelial dysfunction. Chronic inhibition of IL-1 improves LV deformation in parallel with endothelial function and nitro-oxidative stress.